Financial Literacy and Business Sustainability Among Elderly Entrepreneurs: A Systematic Review - Mei Supriyani; Sakti Brata Ismaya; Dinni Agustin; Ignatius Erik Sapta Yanuar (Asian Journal of Social and Humanities, 2026)
Global demographic shifts toward an aging population have resulted in an increasing number of older adults remaining economically active, including through entrepreneurial activities. Financial literacy has emerged as a crucial determinant of entrepreneurial resilience, business sustainability, and economic independence among elderly entrepreneurs. This research aims to identify entrepreneurship interventions implemented for elderly populations, assess the impacts of these interventions on quality of life, social well-being, and active aging, and evaluate the role of financial literacy and digital financial literacy in supporting entrepreneurial activities and sustainable entrepreneurship among older adults. The review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. Searches were conducted in Scopus, PubMed, Web of Science, Dimensions, and Google Scholar for studies published between 2015 and 2026. Methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal framework and risk-of-bias assessment. This research demonstrates that financial literacy is a critical enabler of successful elderly entrepreneurship. Older adults with adequate financial knowledge are better equipped to manage entrepreneurial risks, savings, and investment decisions. Financial literacy was consistently associated with improved business continuity, entrepreneurial resilience, savings behavior, investment decision-making, digital adaptation, and financial independence. Digital financial literacy also enhanced market adaptation and access to financial technologies. Entrepreneurship interventions positively influenced financial independence, social participation, active aging, and psychological well-being among older adults. Financial literacy represents a strategic capability that supports sustainable entrepreneurship among older adults. Nevertheless, stronger longitudinal and experimental studies are needed to establish causal relationships between financial literacy and long-term business sustainability outcomes.